Setu Babakan Setu Babakan: Kampung Betawi dalam Segi Historis: Kebudayaan Betawi, Sejarah Kampung Betawi Setu Babakan, Fungsi dan Manfaat Setu Babakan - Rahmanto Dwi Sasongko; Jumardi (Proram studi pendidikan Sejarah Fakultas Keguruan Dan Ilmu Pendidikan Universaitas PGRI Banyuwangi, 2021)
DKI Jakarta is the capital city of the Unitary State of the Republic of Indonesia which consists of 4 parts, namely North Jakarta, East Jakarta, South Jakarta, and West Jakarta. In the 4 parts of the area, each has a variety of places or destinations that have historical value, one of which is Setu Babakan Kampung Betawi which is located in Jagakarsa, South Jakarta. And this article will discuss about these historical attractions where Setu Babakan has historical traces that are full of meaning and benefits for all of us as well as a source of learning references so as to increase our knowledge. This study uses historiographical methods such as the stages of topic selection, heuristics, results, to historiography or writing. It is hoped that with this article, readers will not only know Kampung Betawi Setu Babakan only as a tourist place but also can be interesting to study.